Empirical Relationship Between Relative Electrical Conductivity And Relative Density Of The Al-Foam Fabricated Through Pressure Assisted Sintering/Dissolution Process - Mamat, Othman; Hussain, P; Mustapha, Mazli; Ismail, Fauzi (2008)
The viability of electrical conductivity as a tool for evaluating variations in morphology of pressure assisted sintering/dissolution Al-foam compacts was investigated. In the preparation of foam specimens, the Al powder and the NaCl (leaching agent) were dry-mixed together in order to prepare homogenously mixture. The blended mixture was then subjected to pressure assisted sintering in which a pressure beyond atmospheric level is externally applied to the specimen during high-frequency induction heated sintering. The embedded leaching agent was then dissolved in order to leave behind an open-celled Al with the same chemical composition as that of the original Al powder. The final material is highly porous and has an interconnected porosity network. The structure of the resulting material has three levels of porosity (i.e. main cells, windows and microporosity). The cell morphology and the size of Al foam closely match those of the leaching particles used. The influence of processing parameters: volume fraction of leaching agent, compaction pressure at elevated temperature, sintering temperature, sintering time and heating rate on the electrical conductivity of the final foams were studied. It was found that all the chosen factors have significant effects on the physical and mechanical properties of the foam and Al volume fraction is the most important parameter affecting the relative electrical conductivity and relative density of the resultant foam. The findings also suggests that the relationship between relative electrical conductivity and density of the specimen does not follow the mathematical description given by Skrohod and Solinin, instead the power law seems to be a good characterization of the relationship between experimental data of electrical conductivity and density of the resultant foams.